THE INVESTIGATION OF MECHANICAL AND PHYSICAL PROPERTIES OF GRANITE, LIMESTONE AND MICROTONALITE AGGREGATES - MAHATHIR, MOHD NOOR (Universiti Malaysia Sarawak (UNIMAS), 2020)
Aggregates are the basic material for every construction that can help build a strong foundation, be it highways or railways. Sarawak's construction industry faces alarming granite shortages due to the massive demand arises from ongoing road construction projects. This research aims to investigate the mechanical properties of aggregate with the effect of wetting and drying cycles on different combinations of granite, limestone and microtonalite aggregates. Throughout this study, granite, limestone and microtonalite aggregates' mechanical and physical properties are studied with different types of aggregate combination design using granite as the main aggregates. Limestone and microtonalite aggregates are selected for modified aggregates as they have potential use in combination aggregate design to reduce the use of granite aggregates in industry. Laboratory work on the Elongation Index Test and Specific Gravity to determine the physical properties of aggregates was the first stage of laboratory testing. The second laboratory stage, the combination of aggregates, was tested for their mechanical properties with Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV) and Los Angeles Abrasion (LAA). The value of granite, limestone and microtonalite aggregate for both controlled and wetting and drying samples for AIV, ACV and LAA has met the standard requirement of Jabatan Kerja Raya, which is below 25% for AIV and ACV and below 45% for LAA. As a result, the combination of granite, limestone and microtonalite aggregates is acceptable and has the potential to be used in industry.